Observations of new particle formation in enhanced UV irradiance zones near cumulus clouds - B. Wehner; F. Werner; F. Ditas; R. A. Shaw; M. Kulmala; H. Siebert (Atmospheric Chemistry and Physics, 2015)
During the CARRIBA (Cloud, Aerosol, Radiation and tuRbulence in the trade wInd regime over BArbados) campaign, the interaction between aerosol particles and cloud microphysical properties was investigated in detail, which also includes the influence of clouds on the aerosol formation. During two intensive campaigns in 2010 and 2011, helicopter-borne measurement flights were performed to investigate the thermodynamic, turbulent, microphysical, and radiative properties of trade-wind cumuli over Barbados. During these flights, 91 cases with increased aerosol particle number concentrations near clouds were detected. The majority of these cases are also correlated with enhanced irradiance in the ultraviolet (UV) spectral wavelength range. This enhancement reaches values up to a factor of 3.3 greater compared to background values. Thus, cloud boundaries provide a perfect environment for the production of precursor gases for new particle formation. Another feature of cloud edges is an increased turbulence, which may also enhance nucleation and particle growth. The observed events have a mean length of 100 m, corresponding to a lifetime of less than 300 s. This implies that particles with diameters of at least 7 nm grew several nanometers per minute, which corresponds to the upper end of values in the literature (Kulmala et al., 2004). Such high values cannot be explained by sulfuric acid alone; thus extremely low volatility organic compounds (ELVOCs) are probably involved here.